Julgamento clínico e autoeficácia de enfermeiros para o manejo da sepse: uso da simulação clínica - Carvalho, Lilian Regina de (2018)
The use of active methodologies has demonstrated efficacy in the teaching and learning process in nursing. Thus, realistic simulation emerges as a strategy that, in addition to allowing real experimentation without the exposure of a patient, allows reflection on the actions developed within the scenario. The aim of the study was to evaluate the efficacy and clinical judgment of nurses for the management of sepsis based on high fidelity clinical simulation. The research was carried out in two stages. In stage I, a methodological study was carried out, with a quantitative approach, consisting of three phases: i) elaboration of the clinical simulation scenario and knowledge test on sepsis; ii) validation of the content by nine judges; and iii) scenario test with nurses . The theoretical framework used was that of meaningful learning. For the construction of the clinical scenario, we chose the Simulation model of the National League for nursing and the content was based on the protocols proposed by the Latin American Sepsis Institute. The analysis of content was given by the Content Validity Index, considering a value> 0.90. In stage II, a quasi-experimental study of the before and after type was performed, consisting of 28 nurses from a teaching hospital. Participants were submitted to three moments of the research: (i) prior to delivery of the study material; (ii) prior to the simulation; and (iii) after the simulation to evaluate clinical judgment, self-efficacy, and knowledge test on sepsis. For the analysis of this step, Spearman correlations and scatter plots were used to compare the relationship of clinical judgment and self-efficacy. The nonparametric Wilcoxon test was used for independent samples and the orthogonal contrasts were applied to compare the times. The results of stage I demonstrated that the instruments were adequate, obtaining general value> 0.90. Nevertheless, some adjustments of the scenario and the test, regarding the clarity of the writing, the functionalities and the pertinence of protocols were changed, according to suggestion of the judges. While in stage II, the mean values at the three times of each outcome were high. The clinical judgment presented a statistically significant difference between the times. The clinical judgment (p = 0.0252) and self-efficacy (p = 0.0269) of the participants in the simulation scenario were statistically higher in relation to the listeners and a strong correlation was found between self-efficacy and clinical judgment (p = 0.001). It is expected that the knowledge test and the clinical simulation scenario on sepsis will be facilitators for teachers and professionals of the permanent / continuing education centers of health institutions in the training of nurses and nursing students. In addition, it is expected that more training with the use of the simulation will be performed with professionals trained for risk-free care, ensuring patient safety.